Dynamics of chromatin accessibility and long-range interactions in response to glucocorticoid pulsing - Stavreva, Diana A.; Coulon, Antoine; Baek, Songjoon; Sung, Myong-Hee; John, Sam; Stixova, Lenka; Tesikova, Martina; Hakim, Ofir; Miranda, Tina; Hawkins, Mary; Stamatoyannopoulos, John A.; Chow, Carson C.; et al. (Genome Research, 2015)
Although physiological steroid levels are often pulsatile (ultradian), the genomic effects of this pulsatility are poorly understood. By utilizing glucocorticoid receptor (GR) signaling as a model system, we uncovered striking spatiotemporal relationships between receptor loading, lifetimes of the DNase I hypersensitivity sites (DHSs), long-range interactions, and gene regulation. We found that hormone-induced DHSs were enriched within ±50 kb of GR-responsive genes and displayed a broad spectrum of lifetimes upon hormone withdrawal. These lifetimes dictate the strength of the DHS interactions with gene targets and contribute to gene regulation from a distance. Our results demonstrate that pulsatile and constant hormone stimulations induce unique, treatment-specific patterns of gene and regulatory element activation. These modes of activation have implications for corticosteroid function in vivo and for steroid therapies in various clinical settings.
10.1101/gr.184168.114